Antipsychotic treatment patterns in refugees and their Swedish-born peers with first-episode non-affective psychosis: findings from the REMAIN study. Issue 3 (4th May 2023) - Spaton Goppers, Julia; Mittendorfer-Rutz, Ellenor; Cullen, Alexis E.; Jamil de Montgomery, Christopher; Tanskanen, Antti; Norredam, Marie; Taipale, Heidi
Abstract : Background: Previous studies suggest that migrants tend to utilise antipsychotics less often than their native-born peers. However, studies examining antipsychotic use among refugees with psychosis are lacking. Aims: To compare the prevalence of antipsychotic drug use during the first 5 years of illness among refugees and Swedish-born individuals with a newly diagnosed non-affective psychotic disorder, and to identify sociodemographic and clinical factors associated with antipsychotic use. Method: The study population included refugees ( n = 1656) and Swedish-born persons ( n = 8908) aged 18–35 years during 2007–2018, with incident diagnosis of non-affective psychotic disorder recorded in the Swedish in-patient or specialised out-patient care register. Two-week point prevalence of antipsychotics use was assessed every 6 months in the 5 years following first diagnosis. Factors associated with antipsychotic use (versus non-use) at 1 year after diagnosis were examined with modified Poisson regression. Results: Refugees were somewhat less likely to use antipsychotics at 1 year after first diagnosis compared with Swedish-born persons (37.1% v . 42.2%, age- and gender-adjusted risk ratio 0.88, 95% CI 0.82–0.95). However, at the 5-year follow-up, refugees and Swedish-born individuals showed similar patterns of antipsychotic use (41.1% v . 40.4%). Among refugees, higher educational level (>12 years), previous antidepressant use and being diagnosed with schizophrenia/schizoaffective disorder at baseline were associated with an increased risk of antipsychotics use, whereas being born in Afghanistan or Iraq (compared with former Yugoslavia) was associated with decreased risk. Conclusions: Our findings suggest that refugees with non-affective psychotic disorders may need targeted interventions to ensure antipsychotic use during the early phase of illness.